Effect of nasal mask oxygenation on incidence of hypoxemia during gastroscopy with propofol sedation in patients at risk of hypoxemia: a prospective randomized controlled study - Wenlong Yan; Liang Yan; Wenjun Meng; Jianyue Cai; Meiping Qian; Yan Zhang; Juan Li; Shuhua Shu; Fang Kang (BMC Anesthesiology)
Abstract Background Hypoxemia is a prevalent complication during sedated gastroscopy and may result in significant adverse outcomes. We aimed to determine if nasal mask oxygenation could decrease the incidence of hypoxemia compared with standard oxygenation in patients with obesity or obstructive sleep apnea (OSA) undergoing gastroscopy under deep sedation. Methods In a prospective randomized study, 120 patients aged 18 to 70 years, diagnosed with obesity or OSA, who underwent sedated gastroscopy, were randomized into two groups: Group M (nasal mask oxygenation) or Group C (nasal cannula oxygenation) from June 2024 to January 2025. The primary outcome was the incidence of hypoxemia (75%≤SpO2 < 90% for < 60 s) during the procedure. Secondary outcomes included the incidences of subclinical respiratory depression (90%≤SpO2 < 95% ) and severe hypoxemia (SpO2 < 75% or 75%≤SpO2 < 90% for > 60 s) during the procedure. Results Nasal mask oxygenation decreased the incidence of hypoxemia from 32.8 to 8.5% ( P < 0.001), subclinical respiratory depression from 48.3 to 20.3% ( P < 0.001), and severe hypoxemia from 13.8 to 1.7% ( P < 0.001). No significant differences in other sedation-related adverse events were observed between the two groups. Conclusion In patients with obesity or OSA, nasal mask oxygenation during gastroscopy with propofol sedation significantly reduced the incidences of hypoxemia, subclinical respiratory depression, and severe hypoxemia without increasing other adverse events. Trial registration Chinese Clinical Trial Registry (ChiCTR2400085162).